2013
DOI: 10.1007/s11783-013-0577-1
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of odor problems in drinking water of major cities across China

Abstract: A comprehensive investigation into the occurrence of odor problem at 111 drinking water treatment plants (DWTPs) in major cities across China was undertaken using both flavor profile analysis (FPA) and gas chromatography-mass spectrometry (GC-MS). Eighty percent of source water samples exhibited odor problems, characterized by earthy/musty (41%) and swampy/septic (36%) odors, while the occurrence rate was lower (45%) in the finished water. Source water from rivers exhibited more pollution-origin odors, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…Though MIB (FOD of 90%) was the most widely distributed odor-causing compounds, geosmin (FOD of 73%) was also frequently detected in this study. These results agree with others suggesting that MIB existed more widely than geosmin in source water of China (Sun et al, 2014). However, we found that the median and the mean concentrations of geosmin were higher than those of MIB, including several exceeding the reference values, but (Sun et al, 2014) detected the concentrations of geosmin lower than that of MIB.…”
Section: Occurrence Assessmentsupporting
confidence: 92%
See 2 more Smart Citations
“…Though MIB (FOD of 90%) was the most widely distributed odor-causing compounds, geosmin (FOD of 73%) was also frequently detected in this study. These results agree with others suggesting that MIB existed more widely than geosmin in source water of China (Sun et al, 2014). However, we found that the median and the mean concentrations of geosmin were higher than those of MIB, including several exceeding the reference values, but (Sun et al, 2014) detected the concentrations of geosmin lower than that of MIB.…”
Section: Occurrence Assessmentsupporting
confidence: 92%
“…These results agree with others suggesting that MIB existed more widely than geosmin in source water of China (Sun et al, 2014). However, we found that the median and the mean concentrations of geosmin were higher than those of MIB, including several exceeding the reference values, but (Sun et al, 2014) detected the concentrations of geosmin lower than that of MIB. Few studies have investigated the other 8 off-flavors in large scale (Chen et al, 2013a,b).…”
Section: Occurrence Assessmentsupporting
confidence: 92%
See 1 more Smart Citation
“…Though reported less frequently, the septic odor caused by compounds such as thioethers and thiols is another important odor type because of its strong impact on human perception (Schiffman et al, 2001;Yang et al, 2008;Yu et al, 2009). These two types of odors have been those most frequently encountered in the source waters of China, according to a nationwide survey (Sun et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…No fishy odor was perceived in the sample from Lanzhou, but a slightly septic/swampy odor was detected. A previous investigation on the occurrence of odor in major cities across China showed that river source waters tend to exhibit pollution-origin odors, while lake/reservoir source waters tend to exhibit algae-origin odors (Sun et al, 2014). Among the six cities, only Lanzhou takes water directly from the Yellow River without a reservoir, which might be the main reason for the lack of fishy odor in the source water.…”
Section: Odor Characteristicsmentioning
confidence: 94%